Exploring and analysing practices and pathways to improve resource use efficiency of crop-livestock farming systems in North-western Bangladesh - Yifan Wang; Groot, Jeroen C.J.; López Ridaura, Santiago; Krupnik, Timothy J. (MFS, 2023)
As the global population continues to grow, the urgency of addressing food sovereignty challenges becomes increasingly apparent. Bangladesh, being a densely populated country, encounters significant hurdles in livestock production sectors the high population density leads to a substantial demand for food, resulting in increased resource requirements. This study aimed to explore and analyse new pathways and practices to improve resource use efficiency of smallholder crop-livestock farms in northwest Bangladesh. Specifically, options to improve manure management and green fodder crop technologies were assessed. The study employed a combination of farming systems characterization, detailed surveys, and model-based methods to assess trade-offs and options for improved livestock management practices. Three study sites were selected based on land size and characteristics with the use of new fodder crops and the production of milk as a key aspect of farming systems. The FarmDESIGN model was utilized for analysis, incorporating a comprehensive database to generate outcomes for each farm. A total of 32 decision variables were established for the multi-objective optimization of three farms, enabling the visualization and analysis of trade-offs and synergies. Trade-offs between improving soil organic matter balances and reducing soil nitrogen (N) loss, as well as between maximizing operating profit and improving soil OM balance were identified. Synergies were also identified, primarily between increasing operating profit and reducing soil N loss, and between reducing feed costs and mitigating GHG emissions. Also, the model results provided alternatives with maximum operating profit and lower animal feed costs by incorporating more on-farm grown fodder area, and specifically an opportunity to increase the area of Jara-1 hybrid grass by 67%. Furthermore, new pathways and practices were proposed to enhance the use of green fodder crops and improve manure management. The adoption of Jara hybrid-1 grass as a new hybrid green fodder crop, in combination with 60% chopped rice straw, was recommended for feeding cows in the study locations. These results demonstrate that smallholder farmers in northwest Bangladesh have the potential to enhance sustainability and resource use efficiency in their crop-livestock farm systems by focusing on improved manure management methods and cultivation and utilization of green fodder crops.